EVALUASI DISTRIBUSI DAN PENGGUNAAN OBAT ASKES DI INSTALASI FARMASI RSUD KOTA BAU-BAU SULAWESI TENGGARA - , Mirnawati Zalili Sailan, Prof. Dr. Marchaban, DESS., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The medicine using at the hospital needs serious attention from hospital management in order it can be used effectively and effeciently. This study aims at giving description and evaluating the medicine using at the distribution phase covering saving and distribution, and the using phase from medical management circle. This study focused on services of health insurance medicine in terms of presenting hospital to face the implementation of SJSN 2014. Since this study used descrptive method, data collection was done by using observation technique, interview, questionnaire, and documentation. The collected data then grouped in both primary and secondary data, and analyzed by using percentage analysis. The result of data analysis was compared with WHO standard and Pudjaningsihâs study (1996). The result of this study were (1) medicine distribution phase shows (a) the percentage of medicine agreement with stock card is 92.65%, (b) the value of Turn Over Ratio is 4.8 times, (d) percentage of expired drug was 0% (e) average service time for non compounding drug prescription and compounding drug prescription were 13.75 minutes and 28.39 minutes, respectively (f) Percentage of served prescribe for outpatient 98.67% and inpatient 91.43%. (2) the phase of medicine using shows that (a) the number of drug items per prescription for outpatient 3.4 item and inpatient 3.5 item (b) the percentage of encounters with an antibiotic prescribed for outpatient 26.58% and inpatient 25% (c) the percentage of encounters with an injection prescribed was 45% (d) the percentage of prescription relevance with the list for outpatient 94.35% and inpatient 92.85% (e) the percentage of drugs adequately labeled was 0% (f) the percentage of patientâs knowledge of correct dosage was 60% - 70% and the patient ability in retelling information from the aphetic employee is 40%.